Attributes of alignment of real estate and facilities management to business needs: An international comparative analysis. Issue 2 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to present a model for consideration of real estate and facilities management (RE/FM) alignment to business needs and to validate the model based on questionnaire surveys carried out in a number of countries around the world.Design/methodology/approach – The model for RE/FM alignment is inspired by the work of the fathers of the Balanced Scorecard in their book called Alignment . The model includes a number of criteria for alignment between business needs, facility solutions, FM services and FM resources. Three multi‐year questionnaire surveys were conducted using the same methodology: the surveys have been carried out in three rounds in different languages: English, Portuguese and Danish. The respondents were senior professionals in the area of FM and real estate/property, mostly working at strategic levels, and representing countries in Asia, Australia, Europe, North America, and South America. The results of the different surveys were combined and then analyzed, using both statistical analysis and tests to validate the results. Differences in the priorities of the alignment criteria in the different regions are described and analyzed.Findings – A main result of the surveys is that all of the alignment criteria were seen as relevant and useful in nearly all countries, but the accorded priorities to the different criteria varied significantly for some of the alignment variables in the different regions. The highest degree of agreement was on "capacity", being the most important criteria for the alignment between supply and demand of facility solutions in relation to business needs. One of the main differences in agreement was between the importance of strategy versus cost in the alignment between "facility solutions" and "FM services".Originality/value – Alignment of RE/FM to business needs is an essential management task and an important tool for RE/FM executives to create added value to their core business. However, there has so far only been limited research into such an alignment concept applicable to FM and an implementation model. Acknowledgements : The authors would like to acknowledge the research funding provided by the Hong Kong Polytechnic University and the efforts of the participants of the expert focus groups and survey respondents.